Analysis Of Theissen Method With IDW Plotting In Kediri City - Sony Susanto; Sigit Winarto; Romadhon (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Rain that falls on the ground is one of the water sources that must be preserved. Great haste can also result in catastrophes, so a mapping estimate is required to determine the flow in a few years using a geographic information system and the isohyet approach with the Arcview application. This investigation’s stage is searching for data in SHP format in the Kediri metropolitan area. The area is plotted using the IDW method by entering precipitation data and coordinates. Then the rainfall relief according to the BMKG classification is obtained using the isohyet approach mapping, indicating that the maximum rainfall level for 2017-2021 will be rather high to moderate. Illustrates a trend in annual maximum rainfall loss.